IMPLEMENTASI LEAN MANAGEMENT PELAYANAN RAWAT JALAN UNTUK MENYEDERHANAKAN BISNIS PROSES PASIEN RAWAT JALAN DENGAN BANTUAN TOOLS SIMRS ABIYOSOFT. - Wahidah, Ayu wahidah; Franciskus Antonius Alijoyo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
In the current era of JKN/BPJS HEALTH, almost every hospital in Indonesia receives health services from BPJS Health participants. The waiting time for hospital outpatients participating in JKN / BPJS has become a national issue and has resulted in many complaints from patients. In overcoming the long waiting time, the JKN / BPJS organizers provide various applications to overcome the long waiting time such as the MOBILE JKN BPJS application and bridging between hospital applications and applications provided by BPJS, but there are still many technical obstacles in the field such as the difficulty of installing the MJKN application from BPJS because it must use otp sms, as well as the patient's lack of understanding about the MJKN application which is less socialized by the hospital, therefore ABIYOSOFT in this case makes a hybridized hospital information system application with BPJS which facilitates and simplifies the outpatient service process. In a good hospital management information system application will provide or simplify the flow with the Lean Management concept